The role of glucocorticoids in increasing cardiovascular risk - Deng, Hai-Wei; Mei, Wei-Yi; Xu, Qing; Zhai, Yuan-Sheng; Lin, Xiao-Xiong; Li, Jie; Li, Teng-Fei; Zheng, Qian; Chen, Jin-Sheng; Ou-Yang, Shun; Huang, Zhi-Bin; Cheng, Yun-Jiu (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Different studies provide conflicting evidence regarding the potential for glucocorticoids (GCs) to increase the risk of cardiovascular diseases. This study performed a systematic review and meta-analysis to determine the correlation between GCs and cardiovascular risk, including major adverse cardiovascular events (MACE), death from any cause, coronary heart disease (CHD), heart failure (HF), and stroke. Methods: We performed a comprehensive search in PubMed and Embase (from inception to June 1, 2022). Studies that reported relative risk (RR) estimates with 95% confidence intervals (CIs) for the associations of interest were included. Results: A total of 43 studies with 15572512 subjects were included. Patients taking GCs had a higher risk of MACE (